Factors Related To The Occurrence Of Type II Diabetes Melitus In The Working Area Of Pasar Ikan Hhealth Center In Bengkulu City - Rahmawati, Nia; Fauzi, Yusran; Darmawansyah, Darmawansyah; Sari, Fikitri Marya; Wulandari, Wulandari (Journal Hygeia Public Health, 2024)
Intoduction: Based on the data from the International Diabetes Federation (IDF), the number of diabetes sufferers worldwide in 2021 reached 537 million. This figure is predicted to continue to rise to 643 million by 2030 and 783 million by 2045. Diabetes mellitus occurs in the age group ≥ 40 years. In Bengkulu City, the highest number of diabetes cases in 2021 was 797, and in 2022 it rose to 3,087 people, with the highest cases being 420 people in the working area of Pasar Ikan Health Center Bengkulu City. This study analyzes the Risk Factors for the Incidence of Type 2 Diabetes Mellitus in the Working Area of Pasar Ikan Health Center Bengkulu City.Method: his research method uses a Cross-Sectional design. The sample size is 54 respondents with a random sampling technique using a questionnaire instrument and data processing using SPSS 22. Data analysis was conducted using the chi-square test with a significance level of 95%. Result and Discussion: he analysis results show that the majority of respondents have light physical activity, are generally aged ≥ 40 years, most respondents are overweight, and the majority of respondents experience Type 2 DM in the working area of Pasar Ikan Health Center Bengkulu City. Based on bivariate analysis, there is a significant relationship between physical activity and the incidence of Type 2 DM, no significant relationship between age and the incidence of Type 2 DM, and a significant relationship between overweight and the incidence of Type 2 DM in the working area of Pasar Ikan Health Center Bengkulu City Conclusion: It is expected that the health center can optimize preventive and promotive programs regarding factors related to the incidence of Type 2 DM and that Type 2 DM sufferers reduce consumption of factors related to the incidence of Type 2 DM and undergo regular check-ups at Pasar Ikan Health Center Bengkulu City